Colds, flu and coughing: Over-the-counter products for pharyngitis and tonsillitis - J. van Schoor (South African Family Practice)
Pharyngotonsillitis is an inflammatory condition of the pharyngeal wall. Respiratory viruses are the major causes of pharyngitis, while bacteria account for 5-30% of cases. Once treatment of the underlying aetiology is considered and addressed, management of pharyngotonsillitis focuses on providing symptomatic relief. A variety of systemic and topical therapies are available. This brief review discusses over-the-counter medicines that may be considered for both adults and children.